PENGARUH OPINI AUDIT GOING CONCERN, PERGANTIAN MANAJEMEN, FINANCIAL DISTRESS DAN UKURAN PERUSAHAAN TERHADAP PERGANTIAN AUDITOR PERUSAHAAN MANUFAKTURYANG TERDAFTAR DI BURSA EFEK INDONESIA - HS, Sri Wahyuni (Universitas Patria Artha, 2024)
This study aims to determine: (1) Effect of Going Concern Audit Opinion on AuditorSubstitution, (2) Effect of Management Change on Auditor Turnover, (3) Effect ofFinancial Distress on Auditor Substitution, (4) Effect of Company Size on AuditorSubstitution in Manufacturing Companies listed on the Indonesia Stock Exchange in2015-2017. This type of research is a comparative causal study with an ex post factoapproach. Samples were taken using purposive sampling technique. The sampleamounted to 67 companies from 136 manufacturing companies listed on the IndonesiaStock Exchange in 2015-2017, so the research data analyzed amounted to 201. The data analysis techniques used were descriptive statistics and logistic regression. Based on the results of this study indicate that (1) Going Concern Audit Opinion variables issued from the Model because of the distribution of Homogeneous date so that it cannot issue results (2) Management Change has a negative and not significant effect on Auditor Substitution, this is indicated by a regression coefficient of - 0,150% and a significance value of 0,719 (0,719 0,05) (3) Financial Difficulties have a negative and significant effect on Auditor Substitution, this is indicated by a regression coefficient of -0,598 and a significance value of 0,044 (0,044 0,05). (4) Company size has a positive and not significant effect on Auditor Substitution, this is indicated by a regression coefficient of -0.013 and a significance value of 0.633 (0.633 0.05).